Influence of dental occlusion conditions on plantar pressure distribution during standing and walking – A gender perspective. (February 2021) - Maurer, C.; Holzgreve, F.; Erbe, C.; Wanke, E.M.; Kopp, S.; Groneberg, D.A.; Ohlendorf, D.
Highlights: Large number of healthy participants of both sexes. Postural control and plantar pressure distribution data were collected on the same group of subjects one after the other. Subjects pressure measuring platform provides quantitative analysis of the postural control and plantar pressure distribution. Abstract: The aim of this study was to investigate gender-specific influences of different symmetric and asymmetric occlusion conditions on postural control during standing and walking. The study involved 59 healthy adult volunteers (41 f/19 m) aged between 22 and 53 years (30.2 ± 6.3 years). Postural control measurements were carried out using a pressure plate by measuring plantar pressure distribution during standing and walking test conditions. Seven different occlusion conditions were tested. Prior to a MANOVA model analysis, the relationship between the two test conditions were checked using a factor analysis with a varying number of factors (between 2 and 10). The plantar pressure distributions during walking and standing are independent test conditions. The coefficient of variance across all variables between the conditions and genders was not significant: t(46) = 1.51 ( p = 0.13). No statement can be made whether, or not, the influence of gender is greater than the influence of the conditions. Healthy male and female test subjects did not show any difference between seven occlusion conditions on the plantar pressure distribution while standing or walking. No differences between the genders were found for any of the investigated variables. In contrast to custom-made occlusion splints, simple cotton rolls appear not to influence the neuromuscular system in a systematic manner.